2013
DOI: 10.3109/02770903.2013.867973
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence, severity and risk factors of asthma, rhinitis and eczema in a large group of Chinese schoolchildren

Abstract: The prevalence of asthma in this study group is low, but the prevalence of rhinitis is high, and could be considered a major public health problem. The prevalence of asthma, rhinitis and eczema is generally higher in boys and younger children generally have higher prevalence of asthma and eczema but lower prevalence of rhinitis. Exposure to pets is a risk factor for rhinitis, being overweight is a risk factor for asthma and rhinitis, and exposure to parental smoking is a risk factor for asthma, rhinitis and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 49 publications
7
34
0
1
Order By: Relevance
“…The 42 records for eczema comprised 24 records from cohort studies , 17 from cross‐sectional studies and one case–control . There were 26 studies from high‐income countries and 14 from middle‐/low‐income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The 42 records for eczema comprised 24 records from cohort studies , 17 from cross‐sectional studies and one case–control . There were 26 studies from high‐income countries and 14 from middle‐/low‐income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The multivariable log-binomial regression model showed a significant association between ETS exposure at home (i.e., presence of 1 or more smokers at home) and atopic dermatitis status after controlling for the effect of gender. Previous studies from China, Germany and Lebanon also reported elevated odds of atopic dermatitis among the schoolchildren if they reported to have been living with smoking family members compared to those who did not have any smoker at home [2,15,17]. The mechanisms by which tobacco smoke affects the skin are poorly understood.…”
Section: Discussionmentioning
confidence: 96%
“…A report from South Africa used the ISAAC phase III instrument and reported the prevalence of ever-atopic dermatitis and current-atopic dermatitis as 14.1 and 9.6%, respectively, and the corresponding figures were higher among female (16.2 and 12.0%) than male (11.8 and 7.0%) adolescents [16]. A Chinese study reported an 11.8% atopic dermatitis prevalence, somewhat higher among male (12.7%) than female (10.9%) students [17]. These nearly comparable results seem to reflect the use of an identical data collection instrument, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…43,48,49 Older studies have not been able to find this association. However, they often use ISAAC criteria to diagnose AD, 33,36,[50][51][52][53][54][55][56] and the most commonly used questions are "Have you ever had an itchy rash which was coming and going for at least 6 months? Have you had this itchy rash at any time in the past 12 months?"…”
Section: Discussionmentioning
confidence: 99%